Neutrophils: Musketeers against immunotherapy - Zahid, Kashif Rafiq; Raza, Umar; Tumbath, Soumya; Jiang, Lingxiang; Xu, Wenjuan; Huang, Xiumei (Frontiers in Oncology, 2022)
Neutrophils, the most copious leukocytes in human blood, play a critical role in tumorigenesis, cancer progression, and immune suppression. Recently, neutrophils have attracted the attention of researchers, immunologists, and oncologists because of their potential role in orchestrating immune evasion in human diseases including cancer, which has led to a hot debate redefining the contribution of neutrophils in tumor progression and immunity. To make this debate fruitful, this review seeks to provide a recent update about the contribution of neutrophils in immune suppression and tumor progression. Here, we first described the molecular pathways through which neutrophils aid in cancer progression and orchestrate immune suppression/evasion. Later, we summarized the underlying molecular mechanisms of neutrophil-mediated therapy resistance and highlighted various approaches through which neutrophil antagonism may heighten the efficacy of the immune checkpoint blockade therapy. Finally, we have highlighted several unsolved questions and hope that answering these questions will provide a new avenue toward immunotherapy revolution.